Conceptualizing sub-national regional cooperation: Coffee Cultural Landscape of Colombia case study. Issue 1 (1st March 2020) - Morales, Diana
Abstract: Regional cooperation is a context-dependent process that is better understood using a geographical approach; this is, accounting for the region as part of the explanation for and not only as the container in which cooperative agreements operate. The case of the Coffee Cultural Landscape of Colombia, a bottom-up regional cooperation process that resulted in a regional trademark, illustrates what roles are played by a diversity of local actors and how local socio-economic conditions influence cooperation agreements. The case highlights the inadequacy of inflexible jurisdictional boundaries and the limitations of preexisting categories (such as inter-municipal cooperation or metropolitan areas). The empirical evidence includes the analysis of 19 semi-structured interviews. Resumen: La cooperación regional es un proceso que depende del contexto local y regional; y una perspectiva geográfica apoya a considerar la región donde ocurre como parte de la explicación, y no como un contenedor dentro del cual operan los acuerdos. Este artículo aborda el caso del Paisaje Cultural Cafetero Colombiano, un proceso de cooperación regional de abajo hacia arriba que resultó en una marca registrada regional. El caso ilustra participantes y roles en el proceso y cómo las condiciones socioeconómicas locales influyen en los acuerdos de cooperación. Los resultados destacan la inflexibilidad de las divisiones jurisdiccionales y las limitaciones de las categorías preexistentes (como la cooperación intermunicipal o las áreas metropolitanas). La metodología incluyó el análisis de 19 entrevistas semi-estructuradas. Résumé: Les processus de coopération régionale dépendent de leur contexte et sont mieux appréhendés à travers une approche géographique. En d'autres termes, il est nécessaire de prendre en compte la région comme partie intégrante de l'analyse, et non uniquement en tant que simple structure où les accords de coopérations se déroulent. Le cas du Paysage culturel du café de Colombie, un processus de coopération régionale du bas vers le haut qui a abouti à la création d'une marque, illustre les rôles joués par une diversité d'acteurs locaux et comment les conditions socio-économiques influencent les accords de coopération. Il met en évidence l'inadéquation des frontières juridictionnelles inflexibles et les limites des catégories préexistantes (comme la coopération inter-municipale et les aires métropolitaines). La méthodologie repose sur une étude de cas et dix-neuf entretiens semi-directifs.